The Association of Breakfast Consumption with Blood Glucose Levels and Short-Term Memory in Primary School Children: A Cross-Sectional Study - Arfah Husna; Hardinsyah Hardinsyah; Cesilia Meti Dwiriani; Lilik Kustiyah (Media Publikasi Cendekia Indonesia, 2026)
Breakfast is an essential component of a healthy diet for school-aged children, yet it is often neglected. This study aimed to analyze the association between breakfast intake, blood glucose levels, and short-term memory among elementary school students in Nagan Raya Regency. This study employed a cross-sectional design involving 150 students from grades IV, V, and VI across three primary schools in Nagan Raya District with a purposive sampling technique. Short-term memory was assessed at 08:30 a.m. using a picture recognition memory test, and blood glucose levels were measured at 09:00 a.m. using the finger-prick method. Breakfast intake was measured using the recall method. Data on student characteristics (gender, daily allowance, and mother’s education) and nutritional status were sourced from the 2023 GENIUS program (Nutrition education and snacks program for school children). The statistical tests used were the Mann–Whitney U test and the Spearman rank correlation test. The results showed that breakfast energy intake was positively and significantly associated with blood glucose levels, and blood glucose levels were positively and significantly associated with short-term memory. Consuming a complete breakfast plays an important role in maintaining stable blood glucose levels and supporting of short-term memory among primary school students.